Speaking Performance in Vocational Students in Rural Area by Using Power Teaching - Yeni Rahmawati; Khusnul Khatimah; Sunarti; Ade Annisa Aulia (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Speaking is one of the crucial skills which has to be learned by non-native students to support their capability in learning a foreign language. Increasing the students’ speaking performance within a middle school is considered crucial as well as in vocational school which requires the students to have specific skills after they graduate. The aim of this study is to identify the influence on the students’ speaking performance by using Power Teaching (PT) Technique. The method of this research applied pre-experimental by involving 36 students from vocational high schools in remote areas. The finding of this research showed that one element of the speaking performance, namely pronunciation, has the highest mean compared to the other element; otherwise, the result of grammar has the lowest mean. However, overall elements have increased compared to the first test it was proved that there was a significant difference in this research. It means that there was an increasing speaking performance among the students who have been given treatments by using Power Teaching (PT).